Impact of Dialysis Method on Colon Postpolypectomy Bleeding in Patients with End-stage Renal Disease - Chiang, Hsueh-Chien; Chiang, Chien-Ming; Lin, Xi-Zhang; Chen, Po-Jun (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Chiang H, Chiang C, Lin X, Chen P. Impact of dialysis method on colon postpolypectomy bleeding in patients with end-stage renal disease. Turk J Gastroenterol. 2024;35(8):677-680.